An Eulerian-based immersed boundary method for particle suspensions with implicit lubrication model. (30th March 2022) - Hori, Naoki; Rosti, Marco E.; Takagi, Shu
Abstract: We describe an immersed boundary method in which the fluid–structure coupling is achieved in an Eulerian framework. The method is an improved extension of the immersed boundary method originally developed by Kajishima et al. (2001), which accounts for the inertia of the fictitious fluid inside the particle volume and is thus able to reproduce the behavior of particles both in the case of neutrally-buoyant objects and in the presence of density difference between the particles and the fluid. The method is capable to handle the presence of multiple suspended objects, i.e.,  a suspension, by including a soft-sphere normal collision model, while the lubrication correction typically added to similar immersed boundary methods in order to capture the sub-grid unresolved lubrication force is here treated implicitly, i.e.,  naturally obtained without any explicit expression, thus no additional computation is required. We show that our methodology can successfully reproduce the rheology of a particle suspension in a shear flow up to a dense regime (with a maximum particle volume fraction around 46%) without any additional correction force. The applicability of this methodology is also tested in a turbulent pressure-driven duct flow at high Reynolds number in the presence of non-negligible inertia and non-uniform shear-rate, showing good agreement with experimental measurements. Highlights: We describe an Eulerian immersed boundary method. The method is suitable to study particle suspensions. The lubrication correction is treated implicitly. The methodology is tested for a particle suspension in a laminar and turbulent flows.